Arteterapia nas paisagens das velhices: Método PREAMAR de intervenção - Pomeranz, Cristiane Tenani (2017)
To approach Art and Old Age, with the interdisciplinary view of Gerontology, is the working method used in this documental research The research is also retrospective, descriptive and qualitative in character and has its main axis in the story of a ballerina named Elisa, whose stage name was Zuzima. After the stroke, and during rehabilitation, she is exposed to Art Therapy, where she finds ways to rescue the potential of life that was lost to the pathology. This research is based on authors from various fields of knowledge, such as Geertz, Tótora, Ciornai, Francisquetti, Carrière, Messy, Beauvoir, Foucault, Nietzsche among others, and features a method of art-therapeutic intervention named PREAMAR. The method consists of seven steps -perception, recognition, strategy, affection, hands-on, result analysis and refinement, and was developed during the professional involvement with Elisa. More than a methodology, Elisa revealed the imminent human frailty, as a condition that is able to stifle the potency of existing life in the elderly, and became what the sociologist Max Weber termed an “ideal type”, an instrument for researching sociological knowledge, a mental construction of the researcher which emphasizes the aspects to analyze in the object of study. Elisa allowed the selection of a series of interventions, building in this manner an “ideal type” that can be perceived in the practical cases of Art Therapy. These interventions were made with elderly people in a large institution of Long-permanence in the city of São Paulo, with elders from the Atelier of Art & Inclusion and Dementia of the project Make Memories, with socially vulnerable elders who attended a public day-Center, and other elders that were attended individually by the researcher, pointing towards an internal movement that was developed in favor of those elders who perceive the possibilities of living the old age. It was observed that Art Therapy is a facilitating tool for the understanding of elderliness, as well as a practice favoring conducts of meaning–of-life for the elderly. By being involved in this method, the elderly can find ways of interpreting the world, to exist inserted in the present time, in which the understanding of facts, of life and of elderliness can be clarified in the midst of the current scenario. The PREAMAR method, learned and replicated, shows to be effective in the transformation of landscapes that, in many old-ages, are devoid of enchantments. For the fragile old-ages , this study proposes an Art Therapy that seeks, in the force of Art and in the PREAMAR method, the conditions to rescue the Zuzimas oppressed by the nihilism that is found in the most diverse forms of growing old